Custom Cementless Femoral Stems in Total Hip Arthroplasty - Wera, Glenn D.; Dwyer, Mark W.; Verhotz, Daniel R.; Popa, Matthew A.; Marcus, Randall E. (The Journal of Hip Surgery, 2019)
Obtaining appropriate prosthetic fit in cementless total hip arthroplasty can be challenging in cases with disparity between the femoral and metaphyseal diameters of the femur or cases of complex deformity. One solution has been to utilize a custom femoral component in total hip arthroplasty. The long-term results of this option with respect to femoral morphology are limited. This cohort was analyzed to determine the survivorship, functional results using Harris Hip Scores (HHSs), and complication rates using these implants. Survivorship and complications were evaluated based on the proximal femoral anatomy and severity of arthritis. The authors retrospectively reviewed 73 cases of custom femoral implants in total hip arthroplasties by a single surgeon. The average age of patients at index surgery was 58.06 years (range, 36.00–73.75 years). The mean follow-up was 8.59 years (range, 0.17–20.33 years) with a minimum of 2-year follow-up required for analysis of HHS data. There were 8 failures at a mean of 67.68 months (range, 2.04–135 months). The reasons for revision were infection (2), osteolysis (1), periprosthetic fracture (3), osteolysis and aseptic loosening (1), and polyethylene wear (1). The mean preoperative HHS was 55.38 (range, 31–90). The mean follow-up HHS was 93.10 (range, 38–100) with a mean improvement of 37.44 (p < 0.0001). Complications included infection (3), fracture (6), and dislocation (3). Preoperative Dorr classification A (n = 44), B (n = 24), and C (n = 1) and Kellgren–Lawrence grades I (n = 0), II (n = 2), III (n = 7), and IV (n = 60) were not predictive of failure or revision (p = 0.45, p = 0.6). There was a near significant association between Dorr classification B femur fractures requiring revision (p < 0.053). Kaplan–Meier predicted survivorship was 20.33 years with revision for any reason as the endpoint and total overall survivorship of 81.7%. Custom cementless femoral stems provide satisfactory survivorship and improvement in hip scores in a variety of patients undergoing cementless total hip arthroplasty. Fracture rates are higher in Dorr class B femurs. The level of evidence was IV.
Keywords: hip; arthroplasty; custom